Autonomous low-cost ozone sensors: development, calibration, and application to study exposure and spatial gradients - Giardina, Dylan M., author; Jathar, Shantanu, advisor; Magzamen, Sheryl, committee member; Volckens, John, committee member; Bechara, Samuel, committee member (Colorado State University. Libraries, 2022)
Ozone (O3), a criteria pollutant and atmospheric oxidant, is not routinely measured in rural and remote environments and hence exposure to ozone pollution in these regions remains poorly understood. In this work, we built, calibrated, and deployed five low-cost, autonomous ozone sensor systems (called MOOS) in Northern Colorado, a region that is non-compliant for O3 during the summertime. Each MOOS included the following components: (i) an Aeroqual SM50, a heated metal oxide ozone sensor, mounted inside a custom radiation shield, (ii) a power system that consisted of a 30 W solar panel, 108 Wh lithium-ion battery, and charge controller, (iii) a Particle Boron to acquire, process, and transmit data to the Cloud, and (iv) an environmental sensor to measure temperature, relative humidity, and pressure. In a three-week long collocated study, we found that all MOOS, calibrated using 48 hours of reference data, compared well against reference monitors with a measurement error between 4-6 parts per billion by volume (ppbv). Manufacturer- and laboratory-based calibrations over- and under-estimated ozone levels at higher and lower ozone mixing ratios, respectively. When deployed in Northern Colorado for an additional three weeks to measure O3 exposure and study O3 trends across an urban-rural gradient, we found that the MOOS, calibrated using data from the collocated study and calibrated using 48 hours of reference data in the field, demonstrated good sensor performance (RMSE of 3.98 - 8.80 ppbv and MBE of 0.22 - 3.82 ppbv). Compared to the collocated study, the field study resulted in larger measurement errors for all five MOOS (RMSE of 3.66 - 4.00 versus RMSE of 3.98 - 8.80). Furthermore, there was modest variability in the field performance across the different MOOS (RMSE < 5 ppbv) that could not be explained by environmental differences between the different sites (e.g., proximity of the MOOS to the reference monitor, land use type, temperature). We found that MOOS were able to capture 100% of non-compliant O3 days during the collocated study and between 25-87% of non-compliant O3 days during the field study depending on the calibration approach used. Furthermore, both reference monitors and MOOS deployed along the east-west corridor in Northern Colorado were able to capture the negative, west-east O3 gradients observed in previous aircraft and modeling studies. Overall, our study indicates that the MOOS shows promise as a low-cost O3 sensor that could be used to supplement routine ambient monitoring and characterize regional ozone pollution.
Keywords: low-cost; calibration; ozone